Intense aerobic training promotes reduction of blood pressure in hypertensive Treinamento aeróbio intenso promove redução da pressão arterial em hipertensos Entrenamiento aeróbico intenso promueve reducción de la presión arterial en hipertensos - dos Santos R.Z.* (2015)
© 2015, Redprint Editora Ltda. All rights reserved.Introduction: Physical training promotes important adaptive responses in the body that decrease morbidity and mortality in hypertensive patients. However, few studies have evaluated the blood pressure response of aerobic training of different intensities in hypertensive patients. Objective: To analyze the effects of intense physical training versus moderate physical training on ambulatory blood pressure in hypertensive patients. Methods: The study included 32 hypertensive patients (aged 48±9 years) randomized as group of aerobic training of moderate intensity (MI), intensity of 60-65% of the heart rate reserve, 40 minutes, three sessions per week (n=12); high-intensity aerobic exercise (HI), intensity of 80-85% of the heart rate reserve (n=12), with the duration adjusted to achieve the same energy expenditure that MI, and a control group (CG) without exercise (n=10). In all three groups the variables ambulatory 24h blood pressure (ABPM) were assessed before and after the eight-week intervention. Results: After the intervention, awake systolic blood pressure (SBP) decreased 10.1mmHg (p=0.024) in HI and 9.7mmHg (p=0.035) in MI and awake diastolic blood pressure (DBP) decreased 12.3mmHg (p=0.002) in HI and 8.4mmHg (p<0.001) in MI. The sleeping SBP reduced 9.5mmHg (p = 0.004) only in AI and 9.8mmHg (p=0.005) in MI. The sleeping DBP reduced 8.2mmHg (p=0.006) in AI and 4.8mmHg (p<0.007) in MI. Systolic and diastolic BP loads of wakefulness and sleep were significantly reduced only in HI. Conclusion: Moderate and intense aerobic exercise training with a duration equalized by caloric expenditure has similar hypotensive effects in hypertensive patients. The pressure load decreased only in HI, thus being intensity-dependent.